Penguatan Kompetensi Guru Non-PLB untuk Penanganan Siswa Berkebutuhan Khusus di Sekolah Dasar Inklusif - Abdul Aziz; Sitti Rohmi Djalilah; Suhirman Suhirman; Rohyana Fitiriani; Husnul Mukti; Dina Apriana (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Inclusive education requires teachers to possess specific competencies to support the learning of students with special needs; however, non-special education (non-PLB) teachers often face challenges in identifying student needs and providing effective guidance. This study aimed to enhance the competence of Special Guidance Teachers (GPK) non-PLB at SDN 4 Pancor and SDN 2 Labuhan Haji through inclusive education training. The training comprised workshops on the concept of inclusive education, student identification and assessment, preparation of individualized learning plans, and guidance strategies for students with special needs. Activities were conducted using lectures, discussions, question-and-answer sessions, and practical demonstrations. The results of this community service program indicated that: 1) the workshop increased teachers’ knowledge of inclusive education; 2) teachers were able to develop learning plans for students with special needs; 3) teachers could create simple forms of identification and assessment; and 4) teachers learned various guidance strategies for students with special needs. The participants’ enthusiasm during the workshop demonstrated a positive response to the program. This training provided practical experience for non-PLB teachers in accommodating the needs of students with special needs and represents a strategic effort to strengthen the quality of inclusive education services at the primary school level.